دارسة كمية ونوعية الهائمات النباتية في المصب العام عند مدينة الناصرية، جنوب العراق - الركابي, حسين يوسف (University of Thi-Qar Journal of Science, 2013)
The current study included a choice of three stations in Al-Masab Al-Aam and samples were collectedin the period from autumn 2011 until the summer 2012. Diagnosed in the current study showed (159)species belonging to 71 genera, and was Bacillariophyceae are prevalent at 73 species belonging to 25genera, represented central 8 kinds belong to 2 genera, and pennales in 65 species belonging to 23 genera,while greens algae was 37 species belonging to 23 genera, blue greens algae represented by 40 speciesbelonging to 17 genera, followed by Euglenophyceae represented by 6 species belonging to 3 genera andyellow algae represented by 2 species belong to 2 genera, while red algae was only one type belong toone genus . Bacillariophyceae fully sovereign associating percentage on items other algae diagnosed atall stations of the three studied was 43% in the St.1 40% in St. 3where as had the lowest rate of 39% inthe St.2, represent the lowest percentage among the varieties of algae Xanthophyceae, recorded 2% in theSt.1 and St.2 but did not, recorded any rate in the St.3. The study showed the presence of (90) species to (52) genera in the first station, and (84) species back to (49) genera in the second station, and diagnosed (91) species back to (43) genera in the third station, and recorded units taxonomic following the highest number of species during the study period (Nitzschia Spp. Oscillatoria Spp. Scenedesmus Spp. and Navicula Spp. )